Study of Sansevieria trifasciata's Morphology, Anatomy, and Leaf in Malang - Winda Aisyah; Nunung Hariyati; Esti Laras Arumingtyas (Natural B, Journal of Health and Environmental Sciences, 2011)
The research had aim to study differentiation of morphology, anatomy, fibers content and fiber strength from leaves of S. trifasciata. The samples were obtained from five different districts in Malang, each varian was taken from three different locations, and each of their leaves was measured its length, width, thickness, and fiber content and fiber strength. Six varian Sansevieria Trifasciata which were found included Sansevieria Trifasciata Prain, S. trifasciata Prain var.laurentii, S. trifasciata varian lilian true oil plastic, and S. trifasciata Varian tiger, S. trifasciata varian moonshine and S. trifasciata varian parva kenya hyacinth. Each of S. trifasciata leaves had special pattern and color. The measurement result showed that the longest, widest, and thickness of leaves was given by S. trifasciata Prain var. laurentii, S. trifasciata varian moonshine and S. trifasciata varian parva kenya hyacinth respectively. S. trifasciata Prain var. laurentii had highest content fibers of leaves, weight of leaves and fibers strength. The anatomy observation showed that fiber xylem diameter of all varian was not significantly different. Sansevieria trifasciata varian tiger had the highest number of fibers